A Complex Condition of Justice in Indonesia: A Book Review ‘Bring Back Justice: Refleksi Kritis atas Isu-Isu Politik, Hukum, dan Keamanan’, M. Nasir Djamil, 2017, Merdeka Book, Jakarta, 224 Pages, ISBN 978-602-61116-2-3 - Rahmawati, Ririn (Indonesian Journal of Advocacy and Legal Services, 2020)
The book entitled Bring Back Justice written by M. Nasir Djamil in 2017. This book explains the writer's personal opinion about justice and law enforcement in Indonesia. Because justice is currently hard to get for the weak people and lack of legal certainty over the rights of the poor people who have been deprived. In addition, this book also discusses about political issues in the State of Indonesia. The related institutions that were discussed in this book such as the KPK, DPR, judges, police and the Indonesian national army.